Large jobs for little devices [microelectromechanical systems]. - Cass, S. (IEEE spectrum)
Microelectromechanical systems (MEMS) may become key components of radio frequency devices, particularly in the mobile marketplace. In filters, they may lower radio size and power consumption while increasing sensitivity. In switches, they could herald the construction of cheaper, electronically steerable antennas for radar and communications applications. MEMS are electromechanical devices with tiny moving parts. They can be built using IC-compatible materials, such as polysilicon, allowing their integration on a silicon chip, side-by-side with semiconductor circuits. Experimental filters are now reaching hundreds of megahertz, and operation up in the gigahertz ranges needed for most wireless and some satellite communications should be feasible. Their ability to kill several birds with one stone is making them very attractive to researchers and developers